Publisher Correction: Dispersal homogenizes communities via immigration even at low rates in a simplified synthetic bacterial metacommunity - Stilianos Fodelianakis (Nature Portfolio, 2019)
In the original version of this article, the green and blue outlines in Figure 2b, top centre and right panels were inadvertently shifted left from the correct position. This has now been corrected in the PDF and HTML versions of the article.